1995
DOI: 10.1164/ajrccm.152.4.7551372
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced arachidonic acid metabolism in alveolar macrophages from wheezy infants. Modulation by dexamethasone.

Abstract: To test the hypothesis that alveolar macrophages (AM) from wheezy infants release increased amounts of eicosanoids, as do AM from adults with asthma, we compared eicosanoid release by unstimulated- and ionophore-A23187-stimulated AM from 13 wheezy and six nonwheezy infants and analyzed its regulation by dexamethasone in vitro. Alveolar macrophages from wheezy infants released greater amounts of thromboxane A2 (TxA2) and leukotriene B4 (LTB4) under resting conditions and of TxA2 upon stimulation than did those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
2
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 26 publications
2
27
2
1
Order By: Relevance
“…Evidence for an increased release of eicosanoids by AMs in adults with asthma is provided by the studies of CHANEZ et al [4] and DAMON et al [5]. In a previous study, we showed that AMs from wheezy infants also spontaneously release increased amounts of eicosanoids, when compared to control children [6].…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Evidence for an increased release of eicosanoids by AMs in adults with asthma is provided by the studies of CHANEZ et al [4] and DAMON et al [5]. In a previous study, we showed that AMs from wheezy infants also spontaneously release increased amounts of eicosanoids, when compared to control children [6].…”
mentioning
confidence: 61%
“…The total number of nucleated cells was 0.38×10 6 (0.28×10 6 -0.41×10 6 ) cells·mL BAL -1 in wheezy children and 0.30×10 6 (0.23×10 6 -0.42×10 6 ) cells·mL BAL -1 in control children (NS). The viability of BAL cells was similar in both wheezy and control children (72 (68-79) % versus 74 (66-77) %; NS) and epithelial cells were always nonviable.…”
Section: Flexible Bronchoscopy and Bronchoalveolar Lavagementioning
confidence: 91%
“…Furthermore, young asthmatic children had increased activated macrophages that released pro-inflammatory mediators (e.g. thromboxan B2, leukotriene-B4 and tumour necrosis factor-a) [41,42]. Protease anti-protease balance may also be altered in asthmatic airways: BALF concentrations of matrix metalloprotease (MMP)9 and tissue inhibitor of metalloprotease (TIMP)1 were found increased [43] or decreased [44] in asthmatic children and positive correlation was reported between MMP9/TIMP1 and nitric oxide output [44].…”
Section: Balfmentioning
confidence: 99%
“…This raises several essential questions such as when does asthma start and can patterns of progression towards persistent disease be individualized? To answer these questions, BAL is likely to represent a useful tool in wheezing infants by documenting the patterns of inflammatory marker expression at various stages of the disease [135,136].…”
Section: Identification Of At-risk Patients To Develop Respiratory DImentioning
confidence: 99%